2018
DOI: 10.14704/nq.2018.16.5.1310
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in university students’ critical thinking following a strategic thinking training program

Abstract: Today's experts believe that critical thinking is a major output in higher education and teaching thinking is a basic point to learning. The aim of this study was to explore whether a strategic thinking training program could improve student's scores on a standardized measure of critical thinking. Sixty-six students aged between 20 and 35 were tested at their college on before the program CCTST and CCTDI. Thirty-nine of these students volunteered to be randomly allocated to the strategic thinking or control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
(21 reference statements)
1
3
0
1
Order By: Relevance
“…In line with the results of the present study, there are several experimental studies suggesting that CT teaching with the general approach (Al-Edwan, 2011 ; Alwehaibi, 2012 ; Arı, 2020 ; Arısoy & Aybek, 2021 ; Eldeleklioğlu & Özkılıç, 2008 ; Karadağ & Demirtaş, 2018 ; Lou, 2018 ; Marin & Halpern, 2011 ; Rahdar et al, 2018 ; Smith et al, 2018 ; Taghinezhad & Riasati, 2020 ), immersion approach (Bağ, 2020 ; Fung & Howe, 2012 ; Jensen Jr., 2015 ; Lopez et al, 2020 ; Marin & Halpern, 2011 ; Reed & Kromrey, 2001 ; Zulkifli & Hashim, 2020 ) and mixed approach (Ku et al, 2014 ; Plath et al, 1999 ; Welch et al, 2015 ) significantly improved CT skills. Also, after examining experimental studies of CT teaching, Tiruneh et al ( 2014 ) concluded that CT skills or dispositions were significantly improved in 80% of studies conducted with the general approach to CT teaching, 55% of studies conducted with the immersion approach to CT teaching and 67% of studies conducted with the mixed approach to CT teaching.…”
Section: Conclusion and Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In line with the results of the present study, there are several experimental studies suggesting that CT teaching with the general approach (Al-Edwan, 2011 ; Alwehaibi, 2012 ; Arı, 2020 ; Arısoy & Aybek, 2021 ; Eldeleklioğlu & Özkılıç, 2008 ; Karadağ & Demirtaş, 2018 ; Lou, 2018 ; Marin & Halpern, 2011 ; Rahdar et al, 2018 ; Smith et al, 2018 ; Taghinezhad & Riasati, 2020 ), immersion approach (Bağ, 2020 ; Fung & Howe, 2012 ; Jensen Jr., 2015 ; Lopez et al, 2020 ; Marin & Halpern, 2011 ; Reed & Kromrey, 2001 ; Zulkifli & Hashim, 2020 ) and mixed approach (Ku et al, 2014 ; Plath et al, 1999 ; Welch et al, 2015 ) significantly improved CT skills. Also, after examining experimental studies of CT teaching, Tiruneh et al ( 2014 ) concluded that CT skills or dispositions were significantly improved in 80% of studies conducted with the general approach to CT teaching, 55% of studies conducted with the immersion approach to CT teaching and 67% of studies conducted with the mixed approach to CT teaching.…”
Section: Conclusion and Discussionsupporting
confidence: 91%
“…Therefore, in order to compare the results of our study with previous research in the literature, the effect sizes associated with the studies with the necessary data were calculated. According to the results of these studies whose effect size was calculated, the general approach (Alwehaibi, 2012 ; Aybek, 2006 ; Lou, 2018 ; Yıldırım, 2010 ) and the immersion approach (Aybek, 2006 ; Şahin, 2016 ; Yuan et al, 2008 ) had a large effect on CT skills.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…En este contexto, el pensamiento crítico parece relevante puesto que es un proceso cognitivo que evalúa de manera racional, lógica y coherente, las opiniones, la información disponible y los recursos en una situación problemática dada; analizando las razones, supuestos, creencias, y arribando a juicios, decisiones y conclusiones mediante un cuestionamiento de los hechos y de los medios de acceso a los mismos (Lou, 2018). En el campo de la educación, el pensamiento crítico permite desarrollar en los estudiantes un conjunto de habilidades esenciales tales como: interpretar, analizar, representar, evaluar, explicar y autorregularse (Facione, 2020), lo que permite postular, conceptualmente, que el desarrollo de estas capacidades influiría en el logro académico, y, en consecuencia, en el desempeño futuro como profesional (Enríquez Canto et al, 2021).…”
Section: Introductionunclassified
“…Today's field experts believe that critical thinking is an important output of higher education and that helping gain critical thinking dispositions is a fundamental part of learning (Bravo et al, 2020;Lou, 2018;Morales Carrero, 2020). For this reason, individuals need to be educated through educational processes by having critical thinking as a cognitive interrogation tool to establish the foundation of a rational and democratic society that provides consistent and useful information (Ennis, 1985;Facione, 1990;Scheffler, 1973).…”
Section: Introductionmentioning
confidence: 99%